The ground and content of Christian hope - Marshall, Brian (1986)
This thesis is an attempt to develop a constructive systematic argument about Christian hope. The first chapter examines the historical ground of Christian hope in Jesus' death and resurrection, the central instance and paradigm of God's saving action. Precisely because it is hope in God who raised Jesus from the dead, Christian hope can face fully those features of life which deny hope and still believe rationally that God's purposes of life and love will triumph. This is shown by discussing hope in terms of atonement and suffering. In chapter two we explore further the historical and theological ground of hope by pressing the importance of understanding Jesus' resurrection as an historical event, and by discussing the trinitarian theology of death and resurrection. We suggest that the theology of Holy Saturday is particularly important since it is an attempt to take seriously Jesus' death as an event within the very life of God. Death itself is an important subject for Christian theology. Christian hope must help people to find positive significance in their mortality as well as trusting in life after death. Moreover, the theological significance of Jesus' resurrection extends far beyond its implications for human destiny since it invites a re-thinking of God, human being and the world. In particular, it paints us to Jesus as God's way of saving the world, and shows the importance of self-sacrifice if hope is to be kept alive. The complex of crucifixion-resurrection is the ground, logic and pattern for the actions of Christian hope. Nevertheless the hope for life after death is essential to Christian hope since it is the hope for the final fulfilment of God's purposes not only for us but for all creation. This shows that eschatology should not be fanciful speculation but rather cautious projection from our present experience of God. We sketch out a possible Christian eschatology in terms of the importance of the body, the social nature of personal life, and the abiding place of creation itself. In chapter three we examine the pressure of the logic of the Christian doctrine of God - ie of the triumph of his grace in crucifixion and resurrection - towards universalism, and find this compelling despite the familiar objections. If all men and women are to love God freely we must think of personal growth towards perfection beyond death. Finally, in chapter four, we turn to the practice of hope in seeking a better human future. We argue that this makes politics an important and unavoidable concern for Christians, and we show why Christian belief requires us to take politics seriously, despite the claims often made, both inside and outside the church, to the contrary. Some indication is given of how the complex relation between faith and politics can be respected, and we make specific proposals for the kind of changes which Christian hope should cause us to work for in contemporary Britain. Thus it may be seen that Christian hope embraces the whole of life in the conviction that all things work together for good under God's love.